MEDICAL APPARATUS AND PROGRAM - ARIYAMA NAOKI; TAKAICHI YOSHIO (2022)
To provide a technique with which, when an operator talks into a microphone, the operator can recognize whether the operator's voice is output from a speaker in a scan room.SOLUTION: A CT apparatus has: an operator microphone 41 installed in an operation room R2 for receiving a voice of an operator 81; a patient microphone 2 installed in a scan room R1 for receiving a voice of a subject 80; a speaker 50 installed in the operation room R2 for outputting the voice of the subject 80 received by the patient microphone 2; a speaker 5 installed in the scan room R1 for outputting the voice of the operator 81 received by the operator microphone 41; and a light-emitting section 31 for, if the patient microphone 2 has received the voice of the operator 81 output from the speaker 5, informing the operator 81 that the operator 81's voice is being output from the speaker 5.SELECTED DRAWING: Figure 18 【課題】操作者がマイクに向かって話しをした場合に、操作者が、スキャンルームのスピーカから操作者の音声が出力されたかどうかを認識できる技術を提供する。【解決手段】ＣＴ装置は、操作ルームＲ２に設けられ、操作者８１の音声を受信する操作者マイク４１と、スキャンルームＲ１に設けられ、被検体８０の音声を受信する患者マイク２と、操作ルームＲ２に設けられ、患者マイク２で受信された被検体８０の音声を出力するスピーカ５０と、スキャンルームＲ１に設けられ、操作者マイク４１で受信された操作者８１の音声を出力するスピーカ５と、患者マイク２が、スピーカ５から出力された操作者８１の音声を受信した場合、スピーカ５から操作者８１の音声が出力されていることを操作者８１に知らせる発光部３１とを有する。【選択図】図１８